Judicial Culture and Social Rights - Rooney, James (Trinity College Dublin. School of Law. Discipline of Law, 2021)
My doctoral thesis explores the conditions under which judicial protection of social rights develops within common law jurisdictions. Social rights relate to material interests necessary for human survival and flourishing, such as the right to adequate shelter, healthcare, water, and education. The judicial protection of social rights is controversial as, for the effective protection of such rights, an unelected judiciary must be capable of directing the elected branches of government to positively expend resources to cure rights breaches. My research is motivated by an interest in how some common law jurisdictions have overcome these objections and enabled social rights to develop into practically enforceable legal claims against the State. I examine the social rights jurisprudence of Ireland and South Africa. Both constitutional texts include express protection for social rights, with South Africa?s Constitution containing considerably more express social rights than Ireland?s. In Ireland, social rights protection has failed to develop, whilst South Africa is arguably the leading common law jurisdiction in regards social rights adjudication. I explore what factors informed the judiciaries in both jurisdictions to adopt divergent attitudes toward social rights. I have conducted an comprehensive overview of the primary materials including constitutional texts and case laws, and secondary materials including academic and extrajudicial commentaries. From a critical engagement with the key cases in both jurisdictions, I argue the crucial determinant for the development of effective social rights protection in common law systems is the dominant cultural attitude within the judicial community to its rights protecting role. In particular, the attitude of the judicial community towards three central contentions ? the importance of judicial rights review, the breadth of its remedial discretion, and the acceptance of social rights as legal rights - determine the likelihood of developing effective social rights protection. My comparative study of Irish and South African constitutional rights law focuses on these three dimensions. I analyse how the attitude of the Irish and South African judiciaries towards judicial review, remedies for rights breaches, and social rights have developed over time, and note the impact which fluctuations in judicial attitudes towards these contentions corresponds with fluctuations in rights protection. By understanding what has informed the Irish judiciary?s restrained attitude to such remedies, and contrasting with the South African jurisprudence the difference in rights protection within the two jurisdictions is explained, and general observations about the impact of judicial culture on rights protection in common law systems will be made. In particular, I show that the disparity in social rights protection between Ireland and South Africa results from diverging judicial attitudes towards the breadth of the remedial power. This supports my thesis that the predominance of particular cultural attitudes within the judiciary determines whether social rights protection can develop within a common law system. In my doctorate, I have endeavoured to state the law as of 28th August 2020.
A Comparative Study of How Social Rights Develop Within Common Law Legal Systems
APPROVED